The Role of USM Economics Students in Facing Global Economic Challenges (Pusat Riset dan Inovasi Nasional, 2026)
The younger generation, as the nation’s future leaders, must be well-prepared to face increasingly complex global challenges. Economics education serves as a fundamental pillar in equipping students with the necessary knowledge, analytical skills, and adaptability to respond to these issues. Economics students, in particular, play a vital role in understanding and addressing global economic challenges through the mastery of microeconomics, macroeconomics, finance, and management. This study aims to analyze the role of economics students at the Faculty of Economics, USM, in enhancing their capacity to support the development of Micro, Small, and Medium Enterprises (MSMEs) through education, training, and the integration of digital technology. A qualitative research method was employed, using a non-probability purposive sampling technique. Data were collected through participant observation, in-depth interviews, and documentation, while data analysis followed the steps of data reduction, data display, and conclusion drawing/verification. The findings reveal that global economic dynamics have a significant influence on the ability of economics students to strengthen MSMEs, particularly by fostering innovation, digital literacy, and collaboration with relevant stakeholders. The study further highlights that economics students can act as agents of change who actively engage in building collaboration, promoting entrepreneurship, and driving innovation to improve market competitiveness. These results imply that strengthening economics education, integrating technology-based learning, and enhancing partnerships with industries are essential strategies to prepare students to contribute effectively to national and global economic development. This research contributes to the discourse on the role of higher education in shaping future economic actors who are capable of responding to global challenges with resilience and innovation.